DEPOIS DA BATALHA: sociedades civis na América Latina - Lucio Fernando Oliver Costilla (Universidade Federal do Maranhão, 2012)
This article explores the expressions of civil society of Latin America in the year 2011 to compare with the positions and functions performed in the first decade of the century which resulted in the progressive advancement of Latin American societies. The analysis shows that even though the last year's struggles had more a local and private horizon than a national and programmatic and politicai one, they are a keyelement in the deepening of anti neo-Iiberal policies for progressive Governments of Latin America and contribute to create a new advanced relationship between civil society and politicai societies in the States of the region.